Application of Techniques PETTLEP Imagery to Increase Karate Athletes' Self-Efficacy - Muna, Muktafia Faidlul; Fadiyah, Salamatun Nisrinal; Yunlistiyana, Erlyta Bilgis; Susanti, Ruth Natalia; Mayangsari, Dewi (Sinergi International Journal of Psychology, 2023)
This research was conducted to evaluate the effectiveness of applying the PETTLEP Imagery technique, with a focus on Physical and Timing aspects, in increasing self-efficacy in non-professional karate athletes. This method involves realistic visualization of movements as well as simulating the duration of movements according to the match situation. The intervention was carried out in the Psychology Building at Muria Kudus University, with a duration of each session of 1–2 hours. The subject involved was a 23 year old female karate athlete who had experience competing from an early age. The implementation method includes physical training combined with visualization of movements and setting the duration according to match time. The results of the activity showed that the subject experienced a significant increase in self-confidence, concentration, and mastery of movements that were more accurate and regular. The combination of Physical and Timing techniques has proven to be effective in increasing the efficiency of movement techniques and reducing anxiety before the match. In conclusion, the PETTLEP Imagery technique can increase athletes' physical and mental readiness in facing competitions, with a positive impact on training performance and reducing anxiety.